(untitled) (Communications in Computational Physics, 2010)
Structural stability and Si-substitution pattern in fullerene cage of C60−nSin are thoroughly investigated by integrating density functional calculations with a colorbond graph (CBG) model. We find that the parameterized CBG model with genetic algorithms can efficiently scan the large configuration space of alloy and therefore identify the low-energy region within the first-principles accuracy. Low-energy (stable) structures of C60−nSin in carbon-rich region (1≤n≤30) were identified and the silicon atoms are found to tend to aggregate in the fullerene cage. The mixing energy of these low-energy structures is ∼ 35 meV/atom and insensitive to the Si concentration. We expect that these alloy fullerene cages can be synthesized experimentally at elevated temperatures.